Clinical study of nodal involvement in carcinoma penis: role of perineural and perivascular invasion in lymph node metastasis - Kumar, P. Ganesh; Venkateswaran, P. (International Surgery Journal, 2018)
Background: Penile malignancies constitute a major health problem in the developing countries especially the Afro Asian countries. It constitutes about 10% of all malignancy. The incidence of the penile malignancy is in decreasing trend in many parts of the world due to improved awareness about the personal hygiene. In this study special effort was made to analyze the histopathological correlation in predicting the lymph node involvement particularly the perivascular and perineural invasion of a tumor on his to pathology and its influence on the lymph node metastasis. Methods: After getting prior ethical committee clearance 42 cases of histopathologically proven cases are included in the study. Those patients included are explained about the nature of the study, investigations that are done. They have also discussed the various treatment options available in Thanjavur medical college. Proper consent in patients own language is obtained before including in the study. Results: The most common histological type found in present study was squalors type. More than 90% (93%) shows squamous variety. Verrucous carcinoma was found in two patients. One patient present with the mixed presentation. Conclusions: Tumour with high grade, high stage, and perineural and per vascular invasion is associated with more nodal metastasis. It is highly recommended to carry out nodal dissection in such types of a tumor. Screening for the early stage of the disease and addressing for the inguinal nodes for the high-risk group will significantly reduce the morbidity and mortality of carcinoma penis.